Psychological, Political, and Situational Factors Combine to Boost COVID-19 Conspiracy Theory Beliefs - Miller, Joanne M. (Can J Polit Sci, 2020)
Conspiracy theories (CTs) are not solely the domain of extremists and paranoids. They cut across demographic and political differences (Uscinski and Parent, 2014) and can have negative social/political consequences. For example, Imhoff and Lamberty (2020) find that belief that the seriousness of COVID-19 is being exaggerated is negatively correlated with self-reported preventative behaviours such as hand washing and social distancing, and belief that the virus was intentionally created by humans is positively correlated with self-reported hoarding of food, sanitary products, and gasoline/oil, as well as stocking up on weapons.